El presupuesto de producción como una herramienta de decisión en la gestión administrativa en el sector bananero - Astudillo Guartatanga, Ruth Elizabeth (2015)
The integration Project was developed through a proper investigation procedure in order to develop a guide that control each of the ítems previously budgeted. Through a plan of economic activity of the company for cover expenses. To develop the guide we have researched and revie wed literatura relating to budgetary control procedures the importance of controlling the liquidity of the company for it´s normal cash flow. In developing it´s activity it is necesary for the institution or company has it´s methodological guide you provide the proper use of money.